2012
DOI: 10.1186/1477-7827-10-113
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative ELISAs for serum soluble LHCGR and hCG-LHCGR complex: potential diagnostics in first trimester pregnancy screening for stillbirth, Down’s syndrome, preterm delivery and preeclampsia

Abstract: BackgroundSoluble LH/hCG receptor (sLHCGR) released from placental explants and transfected cells can be detected in sera from pregnant women. To determine whether sLHCGR has diagnostic potential, quantitative ELISAs were developed and tested to examine the correlation between pregnancy outcome and levels of serum sLHCGR and hCG-sLHCGR complex.MethodsAnti-LHCGR poly- and monoclonal antibodies recognizing defined LHCGR epitopes, commerical anti-hCGbeta antibody, together with recombinant LHCGR and yoked hCGbeta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
17
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 41 publications
4
17
2
Order By: Relevance
“…Unlike hCG, very little is known about how LHCGR modulates its ligand activities in human pregnancy. The presence of hCG-LHCGR and sLHCGR in the blood serum of a pregnant woman has recently been investigated [14,15]. Two ELISA assay systems that specifically measure these two hCG receptor forms (sLHCGR and hCG-LHCGR) in human serum have been applied in prenatal screening [14,15].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Unlike hCG, very little is known about how LHCGR modulates its ligand activities in human pregnancy. The presence of hCG-LHCGR and sLHCGR in the blood serum of a pregnant woman has recently been investigated [14,15]. Two ELISA assay systems that specifically measure these two hCG receptor forms (sLHCGR and hCG-LHCGR) in human serum have been applied in prenatal screening [14,15].…”
Section: Discussionmentioning
confidence: 99%
“…Two ELISA assay systems that specifically measure these two hCG receptor forms (sLHCGR and hCG-LHCGR) in human serum have been applied in prenatal screening [14,15]. Chambers et al [14] reported that circulating hCG-LHCGR appeared to be a unique marker due to two cutoff concentrations: pregnancies with a poor outcome had either very low (≤5 pmol/ml) or significantly high (≥170 pmol/ml) concentrations, in combination with low PAPP-A (<0.8 MoM).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations